Counter maritime terrorism: Multitrack diplomacy - MARIANUS CLAUDIO SAKA MADA; CUT AKHMAD MOEDA DEFRIANDI; SUHIRWAN, S. T. M. M. T; AGUS ADRIYANTO, S. T. M. M (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research aims to discuss the maritime terrorism problem, which researchers see as a national security and sovereignty risk. Terrorist acts committed by maritime groups are a real danger that can jeopardize a country’s safety and independence without its citizens’ knowledge.Method: Researchers in this study employed qualitative and case study research strategies. Qualitative research is a method that gathers information about a topic through in-depth interviews, focus groups, and documenting people’s actions and words. In contrast to quantitative research methods, which emphasize the sample size of the studied population, case study research seeks to gain a deeper comprehension of the issue at hand.Findings: According to these research results, the maritime terrorism group is actively plotting and executing terrorist attacks throughout Southeast Asia. Abu Sayyaf, JI, and the MILF (Moro Islamic Liberation Front) are just a few groups that have publicly stated their intention to oppose western rule in the Philippines. To the tune of Brandt, those terrorist groups on the high seas unleash their full arsenals in acts of terror. Terrorists on the high seas didn’t act because of any ideological commitment to a specific government or religion, unlike ISIS and Al Qaeda.Implications/Novel Contribution: Terrorism cannot be eliminated by any one nation acting alone or the government alone. To defeat terrorism entirely, we need additional resources. Terrorists are human, and as such, they make decisions based on trust and reason, which puts innocent people in danger. While the government’s approach is undoubtedly required, it has only served to restrain the terrorist uprising. Multiple channels of diplomacy are necessary to eradicate terrorism once and for all.